AN ANALYSIS OF USING TABOO WORDS IN THE FASTAND FURIOUS SERIES 6 MOVIE - Fitri Afrilia Fitri Afrilia; Eliwarti Eliwarti '; Novitri Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this descriptive research was conducted in order to find out the taboo words in the fast and furious series 6 movie. The data were collected using the sociolinguistic approach. The data were in the form of utterances, while the contexts of the data were the dialogues uttered by the characters in the movie. The sources of the data were the video of Fast and Furious Series 6 movie and its transcript. The data were collected by selecting dialogues containing taboo words after watching the video and matching the transcript with the video carefully. The primary instrument of this research was a data sheet. The results of this research are stated as follows. Firstly, six of the seven types of taboo words occur in the characters’ utterances in Fast Six movie. They are mother in law, sex, death, excretion, bodily function and religion. From 59 data found in the movie, death has the biggest number of occurrence with 21 times out of total data (35.59%). The smallest number of taboo words’ type is sex and religion with 3 times occurrence (5.08%). Secondly, four functions of taboo words are found in the series namely to show contempt, to draw attention to oneself, to be provocative, and to mock an authority. The most appeared function is to draw attention to oneself with 42 times out of total data (71.18%). The lowest function is to mock authority with only 1 occurrence (1.69%).Key words: Sociolinguistics, Taboo Words, Fast Six Movie